(untitled) (Aporte Santiaguino, 2019)
Capsicum chinense “ají supano” is an ecotype typical of the countryside of Supe very appreciated in the regional cuisine for its aroma and flavor. This ecotype to date has no studies, so the objective of the present study is to characterize it molecularly to identify intragenotypic variability of 30 individuals of chili peppers from the lower Supe river basin using molecular markers ISSR. Fruits were collected from four farmers during the month of November, 2016, being the seeds selected randomly, for their establishment in pots in house mesh. DNA was extracted from three young leaves using the Micro - CTAB method modified by Biotechnology Lab of PIPS in Cereals and Native Crops of UNALM to molecular analysis. Primers SSR 22, UCB 807, UCB 810 and UCB 841 were selected due their high resolution and banding; which did not detect different bands among the individuals evaluated, confirming that it is an autogamous ecotype, all the individuals of the population are genetically equal, therefore there is no intragenotypic variability